The selkie's daughter - Brennan, Linda Crotta (2024)
Brigit, a girl with selkie heritage, embarks on a perilous journey with newcomer Peter to confront the Great Selkie in Sule Skerrie in order to prevent a curse that threatens her village's safety.
Ages 8-12.
Grades 4-6.
Keywords: Selkies -- Fiction; Friendship -- Fiction; Blessing and cursing -- Fiction; Nova Scotia -- Fiction; Novels